MENCIPTAKAN GENERASI PELAJAR YANG AKTIF, PRODUKTIF, DAN PROGRESIF MENUJU INDONESIA EMAS MELALUI SEMINAR PENDIDIKAN - Alit Wiliandani; Asep Somanteri; Siti Mulyati (PT. ABIG RIZKY PUBLISHER, 2026)
This community service activity aims to enhance students’ understanding, motivation, and capacity in developing active, productive, and progressive characteristics as part of the preparation toward Indonesia Emas 2045. The activity was conducted in the form of an educational seminar involving high school students as the main participants, held on November 20, 2025. The implementation method consisted of several stages, including preparation, interactive seminar delivery, evaluation through pre-test and post-test, and follow-up actions. The materials presented covered the importance of active learning, strategies to improve productivity through time management and the effective use of technology, and the development of a progressive mindset in the digital era. The results of the activity indicate a significant improvement in participants’ understanding and engagement during the seminar. Students became more active in discussions, demonstrated better awareness of time management, and showed increased motivation to develop their potential. In addition, participants exhibited a more open, adaptive, and future-oriented mindset. The activity also had a positive impact on building students’ self-confidence and awareness of the importance of education as a means to achieve success. In conclusion, this educational seminar proved to be an effective form of community service in improving student quality. This activity is expected to serve as a replicable and sustainable model to support the development of a competitive and high-quality young generation ready to face global challenges toward Indonesia Emas 2045.